Democracy: vectors of researches in Ukraine - N. M. Onishchenko; L. Yu. Malyuga; M. S. Bulkat (Аналітично-порівняльне правознавство)
The article outlines some current areas of research on Ukrainian democracy. It is noted that in the doctrine of the socio-humanitarian sciences of Ukraine, for a long time the efforts of scientists were concentrated on studying the general problems of the formation of democracy, the authenticity of Ukrainian democracy, the phenomenon of control in the functions of the state, as the basis of the concept of «checks and balances» in democratic states, etc. The provisions on the progress of domestic democracy in the field of the theory of state and law, the history of state and law, constitutional law, political science, etc. are very well developed. Domestic socio-humanitarian sciences have developed a layer of fundamental research, formulations, and conclusions. Currently, the emphasis in the definitions of the concept of «democracy» has shifted somewhat. It was traditionally considered as «the power of the people» or «the rule of the people». The development of the doctrine of socio-humanitarian sciences has ensured the advancement of the scientific understanding of the concept of «democracy» from general categories («people’s power») to its organizational and functional nature: ensuring the principle of democracy and specific instruments of citizen participation in state governance. In this context, it is worth paying special attention to the current areas of research on the study of the features of the implementation of democratic standards in applied spheres of citizens lives – education, medicine, etc. Historical and historical-legal provisions on the authenticity of Ukrainian democracy and its formation have undergone a profound rethinking. The areas of studying the origins of Ukrainian constitutionalism, analyzing experience and rethinking the results of the implementation of democratic standards and approaches in various democratic states remain relevant. Current research directions in a global context relate specifically to contemporary challenges that democracies face. The continuation of the progress of Ukrainian democracy, the deepening of democratic processes in the development of the state and society, and Ukraine’s European integration are taking place in conditions of war. In view of this, research directions on specific mechanisms for maintaining equilibrium, maintaining balances in conditions of war between the legislative, executive, and judicial components of state power, between civil society and the state, and between sectors of civil society in conditions of polarization exacerbated by war are becoming extremely relevant.